Fundraising Strategy Through Beneficiary Testimonial Publication in Strengthening Donor Trust - Nazilah Nazilah (Islam and Social Sciences Review, 2026)
This study examines the fundraising strategy of Al-Mumtaz Berbagi Pontianak, an Indonesian Islamic philanthropic institution, focusing on how program publicity and beneficiary testimonials are used to strengthen donor trust. A qualitative descriptive design was applied. Data were collected through in-depth interviews with the institution's chairperson and head of the fundraising division, selected through purposive sampling, and triangulated with organizational documentation, including activity photographs, videos, and program reports. Data were analyzed using the interactive model of data reduction, display, and conclusion drawing. The institution builds donor trust through two interrelated mechanisms embedded within a structured management cycle: (1) consistent publication of program documentation, which signals transparency and accountability, and (2) dissemination of authentic beneficiary testimonials, which function as social proof and cultivate emotional closeness between the institution, beneficiaries, and donors. As a single-site qualitative case study, the transferability of findings should be interpreted cautiously; future research could adopt quantitative or multi-site comparative designs. The findings offer practical guidance for grassroots Islamic social organizations designing communication strategies that integrate documentary transparency with narrative-based testimonials to sustain donor loyalty. This study contributes to the limited qualitative literature on donor-trust formation in grassroots Indonesian philanthropic institutions by integrating signaling theory and social-proof perspectives within a single explanatory framework, extending prior quantitative research on nonprofit transparency and social media fundraising. Keywords: Fundraising Strategy, Program Publicity, Beneficiary Testimonial, Donor Trust, Islamic Philanthropy.